Development of Interactive Multimedia on Acids and Bases Contextually (IMPAC) Incorporating Multiple Representations - Dwi Rizki Mutiarasani; Muhammad Anarda Wiguna; Tafani Tafani; Suyanta Suyanta (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2025)
The research for the development of the interactive multimedia IMPAC carries important implications for chemistry education, particularly in the topic of acid-base solutions. The contextual approach applied makes the material more relevant to studentsâ€™ daily lives, thereby enhancing their motivation and engagement in learning. Research method 4D Development. Validation by media and content experts, as well as practicality tests by teachers and readability tests by students, respectively, resulted in ideal scores of 95%, 87%, 92%, and 94%. All scores were categorized as â€œVery Good,â€ reinforcing IMPAC's feasibility for broader implementation. Therefore, IMPAC has the potential to serve as an innovative and effective learning medium that not only strengthens conceptual understanding but also fosters a more engaging, interactive, and meaningful chemistry learning experience. The implication for research is to provide recommendations for teaching materials on the acid-base solutions topic.